Optimalisasi Pemanfaatan Hasil Perkebunan Lokal Melalui Inovasi Produk dan Digital Marketing: Keripik Alpukat di Kebun Buah Cipta Rasa Kota Palangka Raya - Ompusunggu, Dicky Perwira; Nasrida, Muhammad; Suherman, Suherman; Simbolon, Tiur; Basunjaya, Buyung Libna; Pratama , Andhika; Hutabaliani , Triputri (Journal of Appropriate Technology for Community Services, 2025)
The optimization of local agricultural products through innovative product development and digital marketing has become essential to enhance economic value and entrepreneurial potential. This study focuses on the production of avocado chips as an innovative and high-value product at the Cipta Rasa Fruit Garden in Palangka Raya. The project involved training and mentoring sessions for local farmers, aimed at improving their skills in processing avocados into chips. The training included product development, digital marketing strategies, and entrepreneurship, addressing the issues of limited avocado shelf life and low economic value. Through this community service activity, participants were equipped with essential entrepreneurial skills such as business planning, product processing, and online marketing, empowering them to utilize local resources effectively. The results showed that the training program significantly increased participants' knowledge and interest in entrepreneurship, as well as enhanced the economic value of avocado products. The digital marketing component also played a key role in expanding market reach and visibility, making the avocado chips a potential flagship product for local economic development.